Nutzerorientierte Planung in Bürogebäuden mit Nachhaltigkeits-Zertifikaten - Buttler, Maike (KIT Scientific Publishing, 2018)
The needs and behavior of building users often differ from the original expectations of building planners; especially in buildings with innovative building technologies. The aim of this study was to explore the design of user participation for certified office buildings, reveal influencing factors and recommend how success factors can be integrated into the German Assessment Scheme for Sustainable Buildings (BNB).